Learning, equilibrium trend, cycle, and spread in bond yields - Guihai Zhao (Bank of Canada, 2020)
Some key features in the historical dynamics of U.S. Treasury bond yields-a trend in long-term yields, business cycle movements in short-term yields, and a level shift in yield spreads-pose serious challenges to existing equilibrium asset pricing models. This paper presents a new equilibrium model to jointly explain these key features. The trend is generated by learning from the stable components in GDP growth and inflation, which share similar patterns to the neutral rate of interest (R-star) and trend inflation (Pi-star) estimates in the literature. Cyclical movements in yields and spreads are mainly driven by learning from the transitory components in GDP growth and inflation. The less-frequent inverted yield curves observed after the 1990s are due to the recent secular stagnation and procyclical inflation expectation.
Keywords: G00; G12; E43; 330; Asset pricing; Financial markets; Interest rates